2022
DOI: 10.1029/2021gl097373
|View full text |Cite
|
Sign up to set email alerts
|

Potential Link Between Ice Nucleation and Climate Model Spread in Arctic Amplification

Abstract: Ice-nucleating particles (INPs) facilitate the formation of ice crystals in clouds by lowering the energy barrier for heterogeneous ice nucleation relative to homogeneous ice nucleation (Rogers & Yau, 1989). Ice crystals commonly coexist with supercooled liquid droplets in mixed-phase clouds at temperatures between 0 and ∼−38°C (Korolev et al., 2017). These clouds are radiatively important, particularly in the Arctic (poleward of 60°N), where they are ubiquitous in the boundary layer (Mioche et al., 2017). Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Due to a lack of observations in the central Arctic relative to other regions, models are typically missing a local source of INPs, specifically those from marine biogenic emissions in the summer 42 , 59 . Recent Earth system model efforts reveal that marine INPs may be important in primary ice formation in Arctic clouds, even more so than dust 60 , More broadly, model spread in estimates of Arctic amplification have even been attributed to their sensitivities to INPs, and specifically summertime INP concentations 61 . However, more observations are needed to further reduce modeling uncertainties associated with INPs and their impacts on Arctic clouds.…”
Section: Resultsmentioning
confidence: 99%
“…Due to a lack of observations in the central Arctic relative to other regions, models are typically missing a local source of INPs, specifically those from marine biogenic emissions in the summer 42 , 59 . Recent Earth system model efforts reveal that marine INPs may be important in primary ice formation in Arctic clouds, even more so than dust 60 , More broadly, model spread in estimates of Arctic amplification have even been attributed to their sensitivities to INPs, and specifically summertime INP concentations 61 . However, more observations are needed to further reduce modeling uncertainties associated with INPs and their impacts on Arctic clouds.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cloud liquid and ice microphysical properties in the present‐day climate can also have a significant impact on the Arctic amplification (Middlemas et al., 2020) and future global climate change (Bjordal et al., 2020; Lohmann & Neubauer, 2018; Tsushima et al., 2006). For example, it has been found that the predicted Arctic amplification strength is highly sensitive to the ice particle size and number concentration of ice nucleating particles in the present‐day environment (Tan & Storelvmo, 2019; Tan et al., 2022). Across the globe, if clouds in the present‐day climate have a lower ice water amount, the phase transition from ice to liquid would be less significant in a future warmer climate, which would result in a weaker negative cloud phase feedback and thus a warmer future climate (Murray et al., 2021; Tan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the freezing efficiency of ice nucleating particles is then used to understand the formation of ice in clouds (e.g., Yang et al, 2013;Fu and Xue, 2017). Their representation in coarse-resolution models even has implications for prediction of Arctic amplification in the climate problem (Tan et al, 2022).…”
Section: Freezing Locations Relative To the Air-water Interfacementioning
confidence: 99%